Tinjauan Kritis Terhadap Perlindungan EBT dalam Hukum Indonesia dan Internasional - Nurdin, Rahmatullah; Ulama, Keyshandrina D.; Moonti, Roy Marthen; Kasim, Muslim A. (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Traditional Cultural Expressions (TREs) are an important part of national identity and intangible cultural heritage that live in indigenous communities in Indonesia. In the midst of globalization and increasing cultural claims by other countries, the urgency of legal protection for TREs is becoming increasingly relevant and strategic. This article aims to examine the effectiveness of legal protection for TREs in Indonesia and to formulate strategies for strengthening protection at the national and international levels. This study uses a juridical-normative approach with literature study techniques and qualitative analysis of laws and regulations, international conventions, and case studies such as Reog Ponorogo and batik. The results of the study indicate that existing legal protection is still limited and has not been able to answer the complexity of cultural claim problems. Harmonization of national law with international standards and collaboration between parties are needed to strengthen Indonesia's legal position in protecting TREs. This study contributes to the development of more responsive and sustainable cultural policies.